One‐Year Mortality After Hip Fracture: Development and Validation of a Prognostic Index. Issue 9 (13th June 2016) - Cenzer, Irena S.; Tang, Victoria; Boscardin, W. John; Smith, Alexander K.; Ritchie, Christine; Wallhagen, Margaret I.; Espaldon, Roxanne; Covinsky, Kenneth E.
Abstract : Objectives: To develop a prediction index for 1‐year mortality after hip fracture in older adults that includes predictors from a wide range of domains. Design: Retrospective cohort study. Settings: Health and Retirement Study (HRS). Participants: HRS participants who experienced hip fracture between 1992 and 2010 as identified according to Medicare claims data (N = 857). Measurements: Outcome measure was death within 1 year of hip fracture. Predictor measures were participant demographic characteristics, socioeconomic status, social support, health, geriatric symptoms, and function. Variables independently associated with 1‐year mortality were identified, and best‐subsets regression was used to identify the final model. The selected variables were weighted to create a risk index. The index was internally validated using bootstrapping to estimate model optimism. Results: Mean age at time of hip fracture was 84, and 76% of the participants were women. There were 235 deaths (27%) during the 1‐year follow up. Five predictors of mortality were included in the final model: aged 90 and older (2 points), male sex (2 points), congestive heart failure (2 points), difficulty preparing meals (2 points), and not being able to drive (1 point). The point scores of the index were associated with 1‐year mortality, with 0 points predicting 10% risk and 7 to 9 points predicting 66% risk. The c‐statistic for the final model was 0.73, with an estimated optimism penalty of 0.01, indicating very little evidence of overfitting. Conclusion: The prognostic index combines demographic, comorbidity, and function variables and can be used to differentiate between individuals at low and high risk of 1‐year mortality after hip fracture.